A safe and effective multi–day colonoscopy bowel preparation for individuals with spinal cord injuries. (4th March 2018) - Song, Shawn H.; Svircev, Jelena N.; Teng, Brandon J.; Dominitz, Jason A.; Burns, Stephen P.
Abstract : Context/Objective : Colonoscopy with polypectomy is associated with a reduced risk of colorectal cancer (CRC), but poor bowel cleansing limits the diagnostic yield of the procedure. Patients with spinal cord injury (SCI) frequently have suboptimal bowel cleansing with standard pre-colonoscopy bowel preparation regimens. We aimed to assess the safety, tolerability, and efficacy of a multi–day inpatient bowel preparation regimen in a population of patients with SCI. Design : Retrospective case series. Setting : VA Puget Sound SCI Center. Participants : All patients with SCI (n = 53) who underwent inpatient colonoscopy at the VA Puget Sound from July 12, 2013 to February 12, 2015. Outcome Measures : Patient characteristics, tolerance of full bowel preparation, pre- and post-bowel preparation electrolyte values, adverse events, and adequacy of bowel cleansing were abstracted. Results : Sixty-eight percent of patients had a cervical level of injury and the majority were either American Spinal Injury Association Impairment Scale A (41%) or D (43%). The full bowel preparation was tolerated by 91% of inpatients. In those with pre- and post-bowel preparation laboratory testing, there were small, but statistically significant decreases in serum calcium and phosphate. No patient had symptoms associated with electrolyte abnormalities or required treatment. Five out of 53 inpatients experienced autonomic dysreflexia (AD) during bowel preparation. Eighty-nine percent of patients had adequate bowel cleansing at colonoscopy. Conclusions : We demonstrate a safe and effective inpatient bowel preparation regimen in a SCI population. The regimen was associated with mild, asymptomatic hypophosphatemia and hypocalcemia. AD was an uncommon event, predominantly occurring in patients who experienced frequent AD episodes at baseline.